Energy intake as a short‐term biomarker for weight loss in adults with obesity receiving liraglutide: A randomized trial - Aditi R. Saxena; Anindita Banerjee; Karen D. Corbin; Stephanie A. Parsons; Steven R. Smith (Wiley, 2021)
Abstract Background and Objective Obesity is a chronic disease associated with many serious comorbidities. Pharmacologic therapies are approved for the treatment of obesity; however, short‐term biomarkers to predict weight loss are not well understood. This study aimed to determine the ability of single‐meal energy intake (EI) to predict weight loss in participants with obesity treated with liraglutide. Methods In this randomized, double‐blind, placebo‐controlled study, participants received subcutaneous liraglutide (titrated to 3.0 mg/day) or placebo once daily, with inpatient assessments at baseline and weeks 3 and 6. The primary endpoint was change from baseline (CFB) in EI during consecutive ad libitum lunch meals at weeks 3 and 6. Secondary endpoints included CFB in 24‐ and 48‐h EI, weight, appetite scores, and gastric emptying measures. Results Sixty‐one participants were randomized (n = 32, liraglutide; n = 29, placebo). The least squares mean (LSM) difference (95% CI; p‐value) in CFB in EI during ad libitum lunch meals between the liraglutide and placebo groups was −236 (−322, −149; p < 0.0001) kcal at week 3 and -244 (−339, −148, p < 0.0001) kcal at week 6. The liraglutide group experienced significant weight loss at weeks 3 and 6, compared with placebo. Weight loss was significantly correlated with EI, but not with appetite score or gastric emptying. Conclusions EI during a single meal is a robust clinical predictor of weight changes in participants with obesity. Future clinical trials can utilize EI at a single meal as a predictor of weight loss.